1990
DOI: 10.1111/j.1432-1033.1990.tb19428.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence of the monomer subunit of the giant extracellular hemoglobin of the aquatic oligochaete, Tubifex tubifex

Abstract: The extracellular hemoglobin of the aquatic oligochaete Tubifex tubifex consists of four subunits: a monomer of 16.5 kDa, a disulfide-bonded trimer of about 50 kDa and at least two subunits of about 30 kDa. The complete amino acid sequence of the monomeric subunit was determined: it consists of 141 amino acid residues and has a molecular mass of 16286 Da including a heme group. 39 residues (28%) were found to be identical with those in the corresponding positions in the monomeric globin chains from Lumbricus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…As shown in Table 1, it has been confirmed that T. tubifex can accumulate metals, in line with previous studies (Singh et al 2007). Iron shows the highest level of concentration, and this is strictly correlated with its biological activity inside the giant globins of oligochaetes (Bailly et al 2007;Stern et al 1990). Other metals, as well transition metals and metalloids, are present in the animal tissues with specific range of accumulation, that in the case of Cr reach a ratio of 10^4 with respect to the water where worms live.…”
Section: Metals Quantificationmentioning
confidence: 94%
“…As shown in Table 1, it has been confirmed that T. tubifex can accumulate metals, in line with previous studies (Singh et al 2007). Iron shows the highest level of concentration, and this is strictly correlated with its biological activity inside the giant globins of oligochaetes (Bailly et al 2007;Stern et al 1990). Other metals, as well transition metals and metalloids, are present in the animal tissues with specific range of accumulation, that in the case of Cr reach a ratio of 10^4 with respect to the water where worms live.…”
Section: Metals Quantificationmentioning
confidence: 94%